Four-faced linga known as the Pancha-mukhi Mahadev - Temples of India Project Team (Jio Institute, 2024)
The four-faced linga, known as the Pancha-mukhi Mahadev, situated in the sanctum of the Harshnath Temple, is actively worshipped at the site. It features three benevolent faces, while the one facing northward is fierce. One face is considered to be at the top of the linga. They collectively represent the Sadashiva form of Shiva. Although the idol is contemporary with the main shrine, there is some disagreement regarding whether it was the original image in the shrine or a later replacement. Ambika Dhaka (2001:377) highlights a strong possibility of it being a later replacement based on two points. 1) According to texts, the fierce face should be facing southward, but here it is oriented towards the north. 2) There is a difference in the circumference of the linga in situ, which is smaller, and the socket, which is larger.